TINJAUAN ATAS PELAKSANAAN KEBIJAKAN DANA DESA - Slamet Widodo; Rastri Paramita (Pusat Kajian Anggaran, 2017)
The share of village funds distribution with a proportion of 90:10, which refers to the Minister of Finance Regulation Number 93 of 2015, inclines to still not convene the principles of justice for most needed villages, especially from the indicator of the number of poor and the status of village progress. Since its implementation beginning in 2015, the village funds have not been able to improve the welfare of the villagers as reflected in the high rates of rural poverty and rising gap levels. Moreover, the data of Desa Membangun Index shows that almost 62 percent of villages comprise of very less and less dveloped villages. These villages are in fact still not getting a larger priority than better-performing villages. In future, the village fund policy should place these villages as the main priority of allocation by considering the variables of the poor and the progress of the village. On the other hand, villages should be given greater flexibility in determining their priorities according to their needs.